On a class of Leibniz algebras - Béré, Côme; Kobmbaye, Aslao; Konkobo, Amidou (International Journal of Advanced Mathematical Sciences, 2015)
We pointed out the class of Leibniz algebras such that the Killing form is non degenerate implies algebras are semisimple.